2020
DOI: 10.1080/02670836.2020.1738071
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformation and microstructure evolution of pearlite heat-resistant steel during heating

Abstract: The phase transformation and microstructure evolution of pearlite heat-resistant steel during heating were observed with an ultra-high temperature confocal scanning laser microscope. The α-ferrite completely disappeared earlier than Fe3C during the formation of γ-austenite, which is inconsistent with the fact that the Fe3C should disappear completely earlier under equilibrium conditions. After the Fe3C + α→γ transformation, static recrystallisation of γ-austenite occurred, accompanied by the dissolution of cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Figure 14 d exhibits the chemical analysis of the precipitates (located at the grain boundaries) via the EDS; it confirms that they are Chromium carbides, as it mainly contains C, Cr, and Mn elements. It was reported that the precipitation of carbide particles on the grain boundaries has pinning effects on the grain growth [ 54 , 55 , 56 ]. Therefore, the precipitated carbides in the TZ work as obstacles for the movement of the grain boundaries, which hinders the coarsening of the grains size at the TZ and works as heterogeneous nucleation sites, which enhances the formation of fine equiaxed structures in the TZ; therefore, the size of the grains at the TZ was finer than the grains which exist at the FB and CGHAZ, which is similar to the results presented in the literature [ 52 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 14 d exhibits the chemical analysis of the precipitates (located at the grain boundaries) via the EDS; it confirms that they are Chromium carbides, as it mainly contains C, Cr, and Mn elements. It was reported that the precipitation of carbide particles on the grain boundaries has pinning effects on the grain growth [ 54 , 55 , 56 ]. Therefore, the precipitated carbides in the TZ work as obstacles for the movement of the grain boundaries, which hinders the coarsening of the grains size at the TZ and works as heterogeneous nucleation sites, which enhances the formation of fine equiaxed structures in the TZ; therefore, the size of the grains at the TZ was finer than the grains which exist at the FB and CGHAZ, which is similar to the results presented in the literature [ 52 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%